The Immigrant Paradox in Children and Adolescents: Is Becoming American a Developmental Risk? 2012
DOI: 10.1037/13094-008
|View full text |Cite
|
Sign up to set email alerts
|

An immigrant advantage in the early school trajectories of Latino preschoolers from low-income immigrant families.

Abstract: The significant rise in immigration that took place at the end of the 20th century and continues into the 21st has resulted in demographic shifts in the composition of the United States and of elementary schools in particular (see Chapter 1, this volume). These changes call attention to the academic achievement and potential of Latino immigrant children, particularly because these children are often categorized as being at risk because of their high likelihood of living in poverty with parents who have lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…In sum, higher family engagement was related to higher language scores, regardless of primary home language, but this distinction was most pronounced among the English subsample. The lack of stark differences among the Spanish-speaking children is reminiscent of the immigrant paradox, or immigrant advantage, evidenced across academic and health outcomes among older Latino students (Suárez-Orozco, Rhodes, & Milburn, 2009), as well as among preschool-aged children (for a review see Palacios, 2012). Our data suggest that higher levels of family engagement in young children’s learning might play a protective role across the board, but especially among English-speaking, low-income Latino families, at least for children who are attending preschool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, higher family engagement was related to higher language scores, regardless of primary home language, but this distinction was most pronounced among the English subsample. The lack of stark differences among the Spanish-speaking children is reminiscent of the immigrant paradox, or immigrant advantage, evidenced across academic and health outcomes among older Latino students (Suárez-Orozco, Rhodes, & Milburn, 2009), as well as among preschool-aged children (for a review see Palacios, 2012). Our data suggest that higher levels of family engagement in young children’s learning might play a protective role across the board, but especially among English-speaking, low-income Latino families, at least for children who are attending preschool.…”
Section: Discussionmentioning
confidence: 99%
“…For example, whereas 26% of White and Asian American 4th graders read below basic levels, nearly 50% of Black, Latino, and American Indian students do so. These early academic gaps are further exacerbated for children of immigrants living in poverty (Palacios, 2012). In 2006, 28% of Latino children in the United States lived in low-income families, as did 33% of immigrant children relative to 17% from nonimmigrant families (see Kids Count Data Center: http://datacenter.kidscount.org).…”
mentioning
confidence: 99%
“…The relatively weak relationships between academic performance from fifth to seventh grade and from seventh to 10th grade suggested that early influences from these mediators almost disappeared between seventh and 10th grade; immigrant students caught up with their peers by seventh grade despite early challenges to their academic success (cf. Crosnoe, 2006, 2012; Han, 2012; Palacios, 2012; C. Suárez-Orozco et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Suárez-Orozco, M. Suárez-Orozco, & Todorova, 2008). Researchers also have reported that, although first generation children may lag behind in early academic performance (perhaps because of language), they may catch up quickly to the academic performance of later generation children because of their motivation to succeed (e.g., Crosnoe, 2006, 2012; Han, 2012; Palacios, 2012; C. Suárez-Orozco et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation